The Success Of The Project Management In light of the Learning Organization Characteristics field reserche for the opinion of simple of worker at the State Commission For Road and Bridge - السامرائي سلوى هاني; دلي علي عبد الحسن (Journal of Economics and Administrative Sciences, 2016)
Abstract The business environment witnessing multiple, rapid changes, and organizations work to find techniques , technology and adoption of concepts which enable it to keep pace with these changes and maintain its survival and growth and continuity, One of these concepts Is Project Management. The research aim to To ensure the projects management success are supposed to identify the factors by teste research variables contribute to it , The Learning Organization Characteristics in the Success Of The Project Management at the State Commission For Road and Bridge . In a community the size of (150) individual and total sample size (43) individual. Proceeding from the problem that has been reflected a number of questions that tries to find the answer ,Premise was planned for the development of research and the formulation of hypotheses and effect link It is the most important of the main hypothesis of the link between learning organization characteristics and the success of Project Management The main effect hypothesis, which states that there is the influence of the characteristics of the learning organization in the success of the project management. For the purpose of obtaining the results of answers researched analysis of the sample, Been using a set of appropriate statistical methods to the nature of the research and its variables, including the percentage table duplicates and the arithmetic mean, standard deviation and Pearson correlation coefficient and simple linear regression. In the light of the results of the answers to the research sample analysis was reached a set of conclusions and the most important of a correlation and effect relationship of significance for most of the organization properties in the success of the project management and accordingly, the most important recommendations is the need to direct the largest of the characteristics of learning organization to influence the success of the project management attention.